On pattern classification and system identification by probabilistic neural networks - Rutkowski, Leszek (1952- ); Gałkowski, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
In the paper probabilistic neural networks are discussed in detail. Neural network structures for non-parametric pattern classification and system identification are developed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka